Analysis of the pyrolysis products from spent bleaching clay - Norzahir, Sapawe; Muhammad Farhan, Hanafi (Elsevier Ltd., 2018)
Malaysia annually generated about 177,000 tonnes of spent bleaching clay (SBC) at 1% clay dosage added which nearly 50,000 tonnes of adsorbed oil was recovered at 28% oil retention. This oil-laden SBC is currently under-utilized as it is dumped in landfills without any attempt to recover the oil. A total of 26.57 wt% of residual palm oil in spent bleaching clay was pyrolyzed using tubular furnace. The pyrolytic oil products analyzed by GC-MS showed aliphatic hydrocarbon ranging from C9-C18 in the main condenser and C16-C44 in the NaCl saturated solution extract. Carboxylic acids and alkanes were the major classes of compounds found in the main condenser and NaCl extract. Significant amounts of monoaromatic compounds, alkenes, alcohols, ketones, aldehydes, esters, nitrogenated compounds, and polycyclic aromatic hydrocarbons (PAHs) were found in this study. The bio-oil resulting from the pyrolysis process gives n-hexadecanoic acid as the major compound